Analisis Peran Pimpinan Dalam Meningkatkan Disiplin Pegawai Di Kantor Camat Alang - Alang Lebar Kota Palembang - Sutinah Andaryani; Sri Ermeila; Rusdi Rusdi; Ida Utami Dwikurniawati (UNIVED Press, 2023)
This qualitative descriptive research was conducted at the Sub-district Office, Alang-alang Lebar Palembang. In collecting the research data, interviews with informants, observation activities and documentation studies were carried out. This research found information that the Sub-district head as the leader had played a good role in improving employees` discipline at the sub-district office Alang-alang Lebar Palembang. The Interpersonal role was carried out by providing model of discipline and giving motivation to his employees. In the informational role, the sub-district head gave freedom in spreading responsible information and conveyed information to his employees in easy way to understand. Furthermore, the role of decision-making showed that the Sub-district head provided opportunities for all employees to be involved and participated in the decision-making process. In addition, there were factors which influenced the increase in employee discipline at the Sub-district Office Alang-alang Lebar Palembang. They were, first, the lack of employees' awareness of obeying the rules. Second, the lack of support in the form of employee promotions. Third, the lack of quality human resources within the organization.